APLIKASI PEMETAAN LOKASI WISATA AIR TERJUN DI PROVINSI BANTEN BERBASIS SISTEM INFORMASI GEOGRAFIS - Ayu Purnama Sari; Saleh Dwiyatno; Agus Irawan; Agung Wulidar Putra (LPPM Unbaja, 2021)
The purpose of this research is to create a mapping application for waterfall tourism locations in Banten Province, using the Geographical Information System (GIS) approach. The research methodology used in this study includes data collection taken with literature studies, interviews, and observations then analysis, system design, programming, testing, and implementation. System design is by using Unified Modeling Language (UML), MySQL database with PhpMyAdmin as a tool for managing MySQL databases, creating program code using Notepad ++, with programming language PHP version 5.6 23, javascipt, database integration with Google Maps API to display map, as well as the browser to check the display generated by the program code through the local server, the results of the application development will be tested for the black box system. The results of this research are the formation of a waterfall tourism mapping application system in Banten Province, which includes information on waterfall tourist locations, facilities and infrastructure around the tour, waterfall features, general information about the waterfall, facilities on the waterfall, information on the route to the waterfall tourist location.